Sexual behavior in Costa Rica and the United States - Rodríguez Arauz, Gloriana (2013)
This study examined differences between Costa Ricans and Euro-Americans in perceptions of appropriate sexual behavior and definitions of sex. When compared to Costa Ricans, Euro- Americans were more likely to consider foreplay, oral sex, and intercourse to be appropriate in the early stages of a relationship. Costa Ricans considered these behaviors to be appro- priate only after steadily dating someone for 3 months or more. Euro-Americans were more likely to consider anal sex and phone/cyber sex to be appropriate prior to serious commit- ment (i.e. marriage). Cultural differences were also found in the types of behaviors that were considered to be sex. Costa Ricans defined non-penetrative acts such as foreplay, oral sex, and phone/cyber sex as sex more often than their Euro-American counterparts. In fact, Euro-Americans rarely considered foreplay or phone/cyber sex to be sex and defined oral sex as sex only in certain contexts. Finally, both Costa Rican and Euro-American partici- pants reported having had more lifetime sexual partners than penile–vaginal intercourse partners. Results are discussed in terms of differing cultural values.